2021
DOI: 10.1055/a-1657-8825
|View full text |Cite
|
Sign up to set email alerts
|

Can Liver Ultrasound Elastography Predict the Risk of Hepatocellular Carcinoma Recurrence After Radiofrequency Ablation? A Systematic Review and Meta-Analysis

Abstract: Purpose The role of liver stiffness (LS) on ultrasound elastography in the prediction of hepatocellular carcinoma (HCC) recurrence after treatment with radiofrequency ablation (RFA) is still unclear. Our aim was to perform a systematic review and meta-analysis to assess whether LS can predict the recurrence of HCC after RFA. Materials and Methods Medline via PubMed, Embase, Scopus, and Cochrane Library databases, and abstracts of international conference proceedings were searched up to June 30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Their results indicated that the liver stiffness value in RFA-treated patients could not effectively predict early HCC recurrence, but it is an independent predictor for late HCC recurrence after curative resection, transarterial chemoembolization (TACE), or RFA treatment. 11,[37][38][39][40] Substantial evidence has confirmed that the mechanisms of early HCC recurrence differ from those of late recurrence post-surgery. 1,3,15 Our current study did not examine the association of alterations in these laboratory parameters with late HCC recurrence, and this topic should be addressed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that the liver stiffness value in RFA-treated patients could not effectively predict early HCC recurrence, but it is an independent predictor for late HCC recurrence after curative resection, transarterial chemoembolization (TACE), or RFA treatment. 11,[37][38][39][40] Substantial evidence has confirmed that the mechanisms of early HCC recurrence differ from those of late recurrence post-surgery. 1,3,15 Our current study did not examine the association of alterations in these laboratory parameters with late HCC recurrence, and this topic should be addressed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that liver ultrasound elastography with liver stiffness could be a reliable tool for predicting recurrence after RFA [ 46 ].…”
Section: Radiofrequency Ablation (Rfa)mentioning
confidence: 99%
“…Recently, a meta-analysis suggested that Ultrasound elastography of the liver stimulates the tissue with ultrasound and extracts parameters related to the elasticity of the tissue in order to display diagnostic information in the image, which could greatly boost prediction performance in the recurrence of HCC after ablation. 16 Few studies have researched the clinical value of postoperative application of Contrast-enhanced computed tomography (CECT) or Non-enhanced CT (NECT).…”
Section: Introductionmentioning
confidence: 99%